2008
DOI: 10.1128/mcb.00923-08
|View full text |Cite
|
Sign up to set email alerts
|

Protein Arginine Methyltransferase 5 Suppresses the Transcription of the RB Family of Tumor Suppressors in Leukemia and Lymphoma Cells

Abstract: The proper epigenetic modification of chromatin by protein arginine methyltransferases (PRMTs) is crucial for normal cell growth and health. The human SWI/SNF-associated PRMT5 is involved in the transcriptional repression of target genes by directly methylating H3R8 and H4R3. To further understand the impact of PRMT5-mediated histone methylation on cancer, we analyzed its expression in normal and transformed human B lymphocytes. Our findings reveal that PRMT5 protein levels are enhanced in various human lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
226
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(234 citation statements)
references
References 44 publications
7
226
0
1
Order By: Relevance
“…1B). BCL2, E2F1and E2F3 have oncogenic roles in tumor proliferation, while RB1 and P53 are tumor suppressor genes (11,12). These genes are common in tumor formation and therefore were chosen for study in K562 cells after cisplatin treatment.…”
Section: Changes In Mrna After Cisplatin Induction Of Apoptosismentioning
confidence: 99%
“…1B). BCL2, E2F1and E2F3 have oncogenic roles in tumor proliferation, while RB1 and P53 are tumor suppressor genes (11,12). These genes are common in tumor formation and therefore were chosen for study in K562 cells after cisplatin treatment.…”
Section: Changes In Mrna After Cisplatin Induction Of Apoptosismentioning
confidence: 99%
“…Protein methyltransferases are being actively pursued as drug targets for various types of cancer where enhanced levels of PRMT5 have been observed (4,(31)(32)(33). Despite the vital role played by PRMT5 in diverse cellular processes, and its potential as a drug target, there has been scant structural information on PRMT5 or its interaction with MEP50.…”
mentioning
confidence: 99%
“…The BRG1-based SWI/SNF complex containing PRMT5 has been found in association with the mSin3A-HDAC2 complex and is implicated in the repression of the MYC target gene cad (carbamoyl-phosphate synthase-aspartate carbamoyltransferase-dihydroorotase) (28). The PRMT5 SWI/SNF complex is also involved in transcriptional repression of ST7, NM23, and retinoblastoma-like protein 2 (RBL2) tumor suppressor genes (27,47). It has been suggested that SWI/SNFassociated PRMT5 is involved in silencing these genes through repressive histone marks including methylation of H3R8 and H4R3 (27,47).…”
Section: Discussionmentioning
confidence: 99%
“…The PRMT5 SWI/SNF complex is also involved in transcriptional repression of ST7, NM23, and retinoblastoma-like protein 2 (RBL2) tumor suppressor genes (27,47). It has been suggested that SWI/SNFassociated PRMT5 is involved in silencing these genes through repressive histone marks including methylation of H3R8 and H4R3 (27,47). In our study, we found that repression of 1,25(OH) 2 D 3 -induced Cyp24a1 transcription by PRMT5 involves recruitment of PRMT5 by BRG1, which is bound to C/EBP␤ at the C/EBP site, and at least in part symmetrical dimethylation of H3R8 and H4R3.…”
Section: Discussionmentioning
confidence: 99%